Evaluation of thermal comfort and carbon dioxide levels during ventricular-assist-device implant - Lembo, Marco; Santoro, Antonio; Andellini, Martina; Losito, Giulia; Olivini, Nicole; Tucci, Mario Graziano; Del Gaudio, Michele (La Medicina del Lavoro, 2017)
Background: Environmental measurements were performed in an operating theatre within a pediatric cardiac department, during a surgical operation involving the use of carbon dioxide for the implantation of a ventricular system (VAD). Objectives: After some reports from the staff, who were complaining about low temperatures in the operating room, it was decided to check carbon dioxide levels, the conditions of thermal comfort and the presence of draughts. Methods: Microclimatic parameters and carbon dioxide concentration were performed with a microclimatic unit Delta OHM model HD 32.1. Results: The carbon dioxide concentration values measured during the operation were below the levels at which the working environment was not comfortable, as expressed by both the ASHRAE (American Society of Heating, Refrigeration and Air Conditioning Engineers) and the ACGIH (American Conference of Government Industrial Hygienists) standards. PMV (Predicted Mean Vote) and PPD (Preticted Pencentage of Dissatisfied) values obtained indicate a thermal discomfort tendency to cold perception, perceived in particular by the anesthesiologist, circulating nurse and cardiovascular perfusionist. Airflow discomforts occurred at different stages of the operation. Conclusions: Acting on the air conditioning system, decreasing air velocity, while guaranteeing the minimum number of air recirculation prescribed by the regulations, appears to be the best prevention measure. Changing the mode of laminar air inlet above the cot may, however, affect the “wash” effect of the operating range. Otherwise, a “protective” measure could concern staff clothes, providing them with garments with better insulation, in order to protect the neck area, which is affected by the effects of draughts.